(untitled) (Global Journal of Medical Research, 2024)
Purpose: COVID-19 mandated emergency remote (online) teaching of dental anatomy at King’s College London. To overcome the challenges of online learning in practical subjects such as dental anatomy, novel approaches to teaching were employed in an attempt to maintain learning quality. Online tutorials were tailored to incorporate technology enhanced learning using digitised lecture slides that emphasised 3-dimensional tooth structures and case-based problem solving along with a key, in-hand, visual aid, namely 1:1 acrylic teeth which were given to each student as a learning accessory. This contemporary online learning format has remained to date. Thus, this work set out to assess the effectiveness of these innovative efforts in online dental anatomy learning and elucidate the key elements that drive learning success. Through this, valuable strategies for improved future course delivery were gained.